19: International market selection and fintech: the role of financial inclusion and perceived corruption in neobank adoption - Karavidas, Dionysios; Paez, Rocio Isabel; Philip, O’Reilly (Edward Elgar Publishing, 2026)
Neobanks have seen significant growth and adoption worldwide in recent years. This study examines the impact of two factors – financial inclusion and perceived corruption – on the success of Neobank adoption in different geographical markets. By analyzing a unique dataset that includes economic data and adoption rates of 90 Neobanks in over 60 countries, we find that both financial inclusion and perceived corruption levels are key in determining the likelihood of successful Neobank adoption in specific markets.